Kinetics of wheat gluten polymerization at extrusion-like conditions relevant for the production of meat analog products. (December 2018) - Pietsch, Valerie L.; Karbstein, Heike P.; Emin, M. Azad
Abstract: Polymerization of wheat gluten influences the product properties of wheat gluten-based, extruded food products such as meat analogs. The aim of this study was to investigate the influence of elevated thermal and mechanical stresses on the polymerization of highly concentrated wheat gluten. A closed cavity rheometer was used to vary thermal and mechanical stresses in a defined manner and at extrusion-like conditions. In the range investigated, evolution of complex viscosity over treatment time indicated a change in wheat gluten polymerization as function of thermal and mechanical stresses. Analysis of SDS-extractable protein under non-reducing and reducing conditions revealed that wheat gluten polymerization was dominated by the formation of disulfide bonds, whereas non-disulfide covalent bonds play a minor role. Mechanical stresses at shear rates up to 50 s −1 had no influence on the formation of covalent bonds. These results indicate that besides the formation of covalent bonds, other molecular interactions contributed to the evolution of complex viscosity during thermomechanical treatment. Finally, an empirical model was set up to describe the polymerization as a function of time, temperature, and shear rate that can be used to give recommendations towards an extrusion process design. Graphical abstract: Highlights: A specific rheometer was used to analyze wheat gluten polymerization. Evolution of complex viscosity depends on thermal and mechanical stresses applied. Wheat gluten polymerization was dominated by formation of disulfide bonds. Mechanical stresses investigated had no influence on formation of covalent bonds. Calculated polymerization kinetics can be used to design extrusion processes.